Olfactory dysfunction in patients undergoing supraorbital keyhole craniotomy for clipping of unruptured aneurysms. Issue 2 (14th December 2019) - Hendrix, Philipp; Fischer, Gerrit; Krug, Julian; Linnebach, Alan‐Christopher; Simgen, Andreas; Griessenauer, Christoph J.; Burkhardt, Benedikt W.; Oertel, Joachim
Abstract : Olfactory performance has rarely been assessed in the perioperative phase of elective aneurysm surgery. Here, we assessed the risk for olfactory deterioration following surgical treatment of unruptured cerebral aneurysm via the supraorbital keyhole craniotomy. A retrospective review of patients with electively treated cerebral aneurysms who underwent perioperative assessment of olfactory function using a sniffin' sticks odor identification test between January 2015 and January 2016 was performed. A subgroup of patients without history of subarachnoid hemorrhage, without prior aneurysm treatment, and confirmed olfactory function underwent supraorbital keyhole craniotomy for aneurysm clipping. Microscopic and endoscopic videos were reviewed for this subgroup. Sixty‐four patients who underwent elective aneurysm treatment either via surgical clipping or endovascular aneurysm obliteration were identified. Prior to treatment, 4/64 (6.3%) demonstrated bilateral anosmia. Collectively, 14 patients (21.9%) met subgroup criteria of supraorbital keyhole craniotomy for aneurysm clipping. Here, olfactory performance significantly decreased postoperatively on the side of craniotomy (ipsilateral, P = 0.007), whereas contralateral and bilateral olfactory function remained unaltered ( P = 0.301 and P = 0.582, respectively). Consequently, 4/14 patients (28.6%) demonstrated ipsilateral anosmia 3 months after surgery. One patient (1/14, 7.1%) also experienced contralateral anosmia resulting in bilateral anosmia. Intraoperative visualization of the olfactory tract and surgical maneuvers do not facilitate prediction of olfactory outcome. The supraorbital keyhole craniotomy harbors a specific risk for unilateral olfactory deterioration. Lack of perioperative olfactory assessment likely results in underestimation of the risk for olfactory decline. Despite uneventful surgery, prediction of postoperative olfactory function and dysfunction remain challenging. Clin. Anat. 33:316–323, 2020. © 2019 Wiley Periodicals, Inc.